2016
DOI: 10.1021/acs.jpcb.6b00399
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Properties and Solvent Effects for All-Atom Solutes in Polarizable Coarse-Grained Water

Abstract: Due to the importance of water in chemical and biological systems, a coarse-grained representation of the solvent can greatly simplify the description of the system while retaining key thermodynamic properties of the medium. A multiscale solvation model that couples all-atom solutes and polarizable Martini coarse-grained water (AAX/CGS) is developed to reproduce free energies of hydration of organic solutes. Using Monte Carlo/free energy perturbation (MC/FEP) calculations, results from multiscale and all-atom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Omitting it reduces the MUE to 1.58 kcal/mol. Since it is known that nitrogen atoms in aromatic rings can be problematic for CM1A charges, 73 it was decided to test as well the original OPLS-AA force field charges of all ligands, which were parameterized by computing the structural and thermodynamic properties of pure organic liquids. 74 The results for the charge perturbation for indole (Supplementary Table S1) suggested that the molecule is too polar with the scaled CM1A charges.…”
Section: Resultsmentioning
confidence: 99%
“…Omitting it reduces the MUE to 1.58 kcal/mol. Since it is known that nitrogen atoms in aromatic rings can be problematic for CM1A charges, 73 it was decided to test as well the original OPLS-AA force field charges of all ligands, which were parameterized by computing the structural and thermodynamic properties of pure organic liquids. 74 The results for the charge perturbation for indole (Supplementary Table S1) suggested that the molecule is too polar with the scaled CM1A charges.…”
Section: Resultsmentioning
confidence: 99%
“…In single-layer schemes, the solvent is described at a unique CG level (figure 1a). Although different schemes for direct coupling of a FG solute with a CG solvent have been proposed, reproduction of relative stability of peptide conformations and hydrogen bond patterns has posed special difficulties to this multi-scale solvation approach [19][20][21]. However, two methods worth highlighting use simple Lennard-Jones (LJ) water models [17] or the ELBA CG solvent [22,23].…”
Section: Fixed Resolutions Single-layer Solvationmentioning
confidence: 99%
“…An alternative approach to implicit solvent models is to treat the solvent explicitly but at a coarser level of resolution, i.e., hybrid QM/MM approaches, ,− or atomistic/coarse-grained (AT/CG) simulations. In a CG representation, multiple atoms are combined into a larger bead that consists of one or more particles (for reviews see, e.g., refs ). For solvents, so-called supramolecular CG models have also been developed where several molecules are represented by a single CG bead. , The description of the interface between the levels of resolution is key in hybrid simulations.…”
Section: Introductionmentioning
confidence: 99%
“…For solvents, so-called supramolecular CG models have also been developed where several molecules are represented by a single CG bead. , The description of the interface between the levels of resolution is key in hybrid simulations. In AT/CG approaches, the AT-CG interactions are either completely reparametrized , or based on standard combination rules , with additional scaling in some cases, as for example in ref .…”
Section: Introductionmentioning
confidence: 99%